Oncotype DX Breast Recurrence Score Distribution and Chemotherapy Benefit Among Women of Different Age Groups With HR-Positive, HER2-Negative, Node-Negative Breast Cancer in the SEER Database - Cheng, Ran; Kong, Xiangyi; Wang, Xiangyu; Fang, Yi; Wang, Jing (Frontiers in Oncology, 2020)
Objective. To explore the relationship between Oncotype DX Breast Recurrence Score (RS) and chemotherapy benefit according to detailed age groups in women with hormone receptor-positive, human epidermal growth factor receptor 2-negative, node-negative (HR+/HER2−/N0) breast cancer. Methods. This was an extensive, comprehensive, population-based retrospective cohort study. Data on individuals with breast cancer were obtained from the Surveillance, Epidemiology, and End Results Program. The cohort was divided into five groups by age (≤35, 36-50, 51-65, 66-80, >80 years). Clinical characteristics and prognostic information were compared between age groups. Results. The study cohort comprised 19,835 patients and the largest age group was 51-65 years (n=9,623; 48.5%). The percentage of patients at low risk RS (0-10) increases with age, whereas those at intermediate-risk RS (11-25) decreases with age (P<0.05). The age group with the highest proportion of patients receiving chemotherapy was ≤35 years, whereas the age group with the lowest proportion was >80 years. The RS thresholds for a survival benefit from chemotherapy differed among different age groups. Statistically significant differences of survival started to emerge from RS≥27 in the group aged ≤35 years, from RS≥25 in the group aged 36-50 years, from RS≥16 in the group aged 51-65 years, and from RS≥29 in the group aged 66-80 years. However, in the group aged >80 years, there was no significant difference even when RS≥31. Conclusions. In the present study, we identified the clinical characteristics, RS distributions, and status regarding receipt of chemotherapy of patients with HR+/HER2−/N0 breast cancer according to detailed age groups, and explored the relationship between RS and clinical features. Additionally, we preliminarily identified the RS thresholds in each age group, which may help in making individualized clinical decisions.